Transformasi Kebijakan Pendidikan Inklusif untuk Meningkatkan Kualitas SDM dan Daya Saing Indonesia - Wahyuni, Sri Intan; Handoyo, Eko; Rokhman, Fathur; Mariyani, Mariyani; Alfansyur, Andarusni (Jurnal Pendidikan Madrasah, 2026)
The transformation of inclusive education policy has become a strategic issue in improving the quality of human resources and enhancing Indonesia’s global competitiveness in an increasingly dynamic and competitive environment. This study aims to analyze the transformation of inclusive education policies and their implications for improving human resource quality and national competitiveness. The research employs a qualitative approach using a literature review method, collecting data from national journal articles, academic books, and relevant policy documents, which are then analyzed systematically through content analysis. The findings reveal that although Indonesia has established a strong regulatory framework for inclusive education, its implementation still faces significant challenges, including limited human resources, inadequate infrastructure, and low public awareness of inclusive education concepts. Furthermore, the study identifies that effective policy transformation requires a systemic approach involving policy reformulation, capacity building of educators, integration of digital technology, and multi-stakeholder collaboration. The proposed policy transformation model serves as a strategic framework to bridge the gap between policy and practice. In conclusion, the transformation of inclusive education policy plays a crucial role in developing high-quality, adaptive, and globally competitive human resources, and therefore must be implemented in a sustainable and integrated manner.